2015
DOI: 10.1002/jmr.2441
|View full text |Cite
|
Sign up to set email alerts
|

The galactose‐binding lectin isolated from Bauhinia bauhinioides Mart seeds inhibits neutrophil rolling and adhesion via primary cytokines

Abstract: In this study, the amino acid sequence and anti-inflammatory effect of Bauhinia bauhinioides (BBL) lectin were evaluated. Tandem mass spectrometry revealed that BBL possesses 86 amino acid residues. BBL (1 mg/kg) intravenously injected in rats 30 min prior to inflammatory stimuli inhibited the cellular edema induced by carrageenan in only the second phase (21% - 3 h, 19% - 4 h) and did not alter the osmotic edema induced by dextran. BBL also inhibited carrageenan peritoneal neutrophil migration (51%), leukocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…A number of other studies also detail important lectin‐mediated binding interactions during PMN trafficking. For example, macrophage galactose type lectin 1 deficiency is associated with increased neutrophilia and hyperinflammation during gram negative pneumonia, while the Galactose‐binding Bauhinia bauhinioides lectin inhibits PMN peritoneal adhesion and migration in response to cytokines including TNF‐α In addition, it has been reported that other lectins including Concavalin A and peanut agglutinin lectin stimulate a chemotactic response in human neutrophils . However, these studies did not identify the specific neutrophil glycoproteins that are the binding targets for these lectins.…”
Section: Discussionmentioning
confidence: 99%
“…A number of other studies also detail important lectin‐mediated binding interactions during PMN trafficking. For example, macrophage galactose type lectin 1 deficiency is associated with increased neutrophilia and hyperinflammation during gram negative pneumonia, while the Galactose‐binding Bauhinia bauhinioides lectin inhibits PMN peritoneal adhesion and migration in response to cytokines including TNF‐α In addition, it has been reported that other lectins including Concavalin A and peanut agglutinin lectin stimulate a chemotactic response in human neutrophils . However, these studies did not identify the specific neutrophil glycoproteins that are the binding targets for these lectins.…”
Section: Discussionmentioning
confidence: 99%
“…A number of other studies also detail important lectin mediated binding interactions during PMN trafficking. For example, Macrophage galactose type lectin 1 deficiency is associated with increased neutrophilia and hyperinflammation during gram negative pneumonia (58), while the Galactose binding Bauhinia bauhinioides lectin inhibits PMN peritoneal adhesion and migration in response to cytokines including TNF-α (59). In addition, it has been reported that other lectins including Concavalin A and peanut agglutinin lectin stimulate a chemotactic response in human neutrophils (60).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research shows that lectin exhibits promising control over tumor cell metastasis by inducing programmed cell death. This potentially offers antiinflammatory properties via the lectin domain in legumes, and demonstrates immunomodulatory effects [234][235][236][237][238]. Additionally, these proteins demonstrate antifungal action and generation of cytokines in both in vitro and in vivo [239][240][241].…”
Section: Uses Of Antinutritional Factors In Research and Future Direc...mentioning
confidence: 99%